Application of the FDTD Hybrid “M3d24-Yee”for simulating EM scattering from two objects separated by long distances - Abd-El-Raouf, Hany E.; El-Diwani, Esam A. (2007)
In this paper we present the application of the hybrid "M3d24-Yee" with subgridding algorithm for solving problems of the electromagnetic radiation or scattering from multiple objects separated by long distances. The large distances between the objects is simulated using the M3d24 with low-resolution grid while the objects and the surrounding regions around the objects are simulated using the Yee algorithm with high resolution. For a test case of scattering from two PEC parallelepipeds the memory required for the M3d24-Yee scheme is found to be less than 10% of the memory required for the Yee algorithm to solve the same problem